Calcinosis Cutis Confined to the Dermis after Intravenous Administration of a Calcium Preparation: A Case Report and Review of the Japanese Literature - Soko Watanabe; Takeaki Shioda; Ken Kobayashi; Sumiko Ishizaki; Fumio Ito; Mariko Fujibayashi; Masaru Tanaka (Karger Publishers, 2014)
A 61-year-old female received intravenous injection of calcium chloride after common iliac artery bypass surgery. A red flare appeared at the site of the intravenous infusion on the left forearm and gradually progressed to induration. Seven weeks later, she was referred to the Department of Dermatology for management. Physical examination showed an indurated plaque measuring 13 × 65 mm in size, with linearly distributed ulcers covered by yellowish-white substance, surrounded by reddish skin. Laboratory tests showed no significant abnormalities including serum calcium, phosphate and thyroid hormones. Cultures were negative for microorganisms. Histopathological examination showed calcium deposition confined to the dermis. The lesion healed spontaneously within 2 months with scar formation. A review of the Japanese literature showed confinement of calcium deposits to the dermis in most of the reported cases. We speculate that the pathomechanism of dermal calcinosis includes needle-induced tissue injury with capillary destruction, leading to release of excess calcium between collagen fibers, and its binding to phosphate in the dermis and deposition as calcium phosphate crystals.